Examining the Food and Nutrition Literacy Levels of Middle School-Aged Children - Haylı, Çiğdem Müge; Avcı, Mehmet Zeki; Chung, Seockhoon; Demir Kösem, Dilek (The European Research Journal, 2026)
Objectives: This cross-sectional study was conducted to examine the food and nutrition literacy levels of middle school children. Methods: Data required for the study were collected online between January 22, 2025, and April 20, 2025. The study group consisted of middle school-aged children. Data were collected using an online survey method using the Socio-Demographic Data Collection Form and the Food and Nutrition Literacy Scale for Children (FNLSC) from 374 middle school-aged children who volunteered for parental consent and were selected using a non-probability sampling method. The statistical analysis of the data obtained in the study was carried out using SPSS 27.0 data analysis software, which employed the following methods: T-test, Oneway Anova, and Kolmogorov-Smirnov test. Results: Of the middle school students participating in the study, 60.2% (n=225) were males and 39.8% (n=149) were female students, with a higher proportion of male students participating. The reliability coefficient of the food and nutrition literacy scale for children was found to be 0.55, while the harmful consumption subscale was 0.45, the packaging reading subscale was 0.50, the beneficial consumption subscale was 0.45, and the interaction subscale was 0.50. In examining food and nutrition literacy levels, significant differences were found within the subscale based on age, gender, grade, family, and nutritional status, but these differences were not statistically significant (P>0.05). Conclusions: In the study examining the food and nutrition literacy levels of middle school children, no differences were found based on some variables. It is recommended that research be conducted to examine children's food and nutrition literacy levels by considering different factors.